Actual Versus Suitable City Position: Case Study of the City of Magadan - Romanova, Natalia A. (International Review of Management and Marketing, 2016)
The achievement and preservation of the stable socioeconomic status of the city aims at increasing its competitiveness and living standards, which is the general goal of urban development. Within this framework, the marketing of the territory is the part and parcel in the public authorities’ activity. In addition to the above, the development of the promotion program, its positioning (as a tool of the city marketing), its transmission to domestic and international economic, sociocultural city policy requires system analysis of pros and cons of the municipal district, threats to its development, its possibilities in the market competition. The study uses the method of SWOT-analysis for elucidation of the critical factors regarding the international and domestic urban development. Research results are presented to the city authorities as the key recommendations in the direction of branding activities of the city of Magadan. Keywords: urban development, Far North-East of Russia, territorial marketing JEL Classifications: M31, M38, R58